The Kinase ERULUS Controls Pollen Tube Targeting and Growth in Arabidopsis thaliana - Schoenaers, Sébastjen; Balcerowicz, Daria; Costa, Alex; Vissenberg, Kris (Frontiers in Plant Science, 2017)
In this paper, we describe the role of the receptor-like kinase ERULUS (ERU) in PT growth of Arabidopsis thaliana. In silico analysis and transcriptional reporter lines revealed that ERU is only expressed in pollen and root hairs (RHs), making it a tip growth-specific kinase. Deviations from Mendelian inheritance were observed in the offspring of self-pollinated heterozygous eru plants. We found that in vivo eru PT targeting was disturbed, providing a possible explanation for the observed decrease in eru fertilization competitiveness. Extracellular calcium perception and intracellular calcium dynamics lie at the basis of in vivo pollen tube (PT) tip growth and guidance. In vitro, ERU loss-of-function lines displayed no obvious PT phenotype, unless grown on low extracellular calcium ([Ca2+]ext) medium. When grown at ½ the normal [Ca2+]ext, eru PTs grew 37% slower relative to WT PTs. Visualization of cytoplasmic [Ca2+]cyt oscillations using the Yellow Cameleon 3.6 (YC3.6) calcium sensor showed that, unlike in WT PTs, eru apical [Ca2+]cyt oscillations occur at a lower frequency when grown at lower [Ca2+]ext, consistent with the observed reduced growth velocity. Our results show that the tip growth-specific kinase ERULUS is involved in regulating Ca2+-dependent PT growth, and most importantly, fertilization efficiency through successful PT targeting to the ovules.